Diagnostic value of cystatin C in patients with drug-resistant pulmonary tuberculosis receiving palliative care - Raznatovska, O. M.; Khudiakov, H. V. (Zaporozhye Medical Journal, 2019)
To date there are no data on the study of heart failure early diagnostic criteria in patients with pulmonary drug-resistant tuberculosis (DRTB) available in the literature. The purpose of the work is to determine the level of serum cystatin C in patients with pulmonary DRTB receiving palliative care and to establish the diagnostic value of this indicator in the early diagnosis of heart failure. Materials and methods. Patients of the main group received palliative care were divided into 2 groups depending on the body mass index (BMI): the main group 1 consisted of 26 patients with BMI ≤18.1 kg/m2, the main group 2 was composed of 26 patients with BMI >18.1 kg/m2. The control group included 29 patients who received antimycobacterial therapy by category 4 according to the drug resistance profile. The level of serum cystatin C was measured by an enzyme-linked immunosorbent assay (ELISA) using the kit “Human Cystatin C ELISA BioVendor Research and Diagnostic Products” (ng/ml; Czech Republic). The serum level of TNF-α was studied by ELISA in a reader Sirio S using the kit “Bender MedSystems GmbH” (Austria), (pkg/ml). The results of the study were processed on a personal computer using statistical software package Statistica, version 13 (Copyright 1984–2018 TIBCO Software Inc. All Rights reserved. License No. JPZ8041382130ARCN10-J). Results. In patients with pulmonary DRTB receiving antimycobacterial therapy, the level of cystatin C exceeds the upper limit of the normal reference values, and in palliative care DRTB patients with BMI >18.1 kg/m2 it is 10,4 % higher than in pulmonary DRTB patients receiving antimycobacterial therapy. At the same time, in patients with pulmonary DRTB receiving antimycobacterial therapy, an increase in serum cystatin C level is significantly associated with a decrease in serum TNFα levels and an increase in BMI. In palliative care patients with DRTB and BMI >18.1 kg/m2, an increase in serum cystatin C levels significantly depends directly on a decrease in serum TNFα. And in palliative care patients with pulmonary DRTB and BMI ≤18.1 kg/m2, a decrease in cystatin C level significantly depends directly on a decrease in BMI and inversely depends on an increase in serum TNFα level, which leads to a significant decrease in the overall quality of life score and heart failure progression. Conclusions. In palliative care patients with DRTB and BMI >18.1 kg/m2, increased level of cystatin C can serve as an early marker of heart failure development. In palliative care patients with DRTB and BMI ≤18.1 kg/m2, low level of cystatin C can serve as a marker of secondary cardiovascular disease development and heart failure progression.